2006
DOI: 10.1140/epjb/e2006-00319-2
|View full text |Cite
|
Sign up to set email alerts
|

Beam splitter for spin waves in quantum spin network

Abstract: We theoretically design and analytically study a controllable beam splitter for the spin wave propagating in a star-shaped (e.g., a Y -shaped beam) spin network. Such a solid state beam splitter can display quantum interference and quantum entanglement by the well-aimed controls of interaction on nodes. It will enable an elementary interferometric device for scalable quantum information processing based on the solid system.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 19 publications
(16 reference statements)
0
24
0
Order By: Relevance
“…Spin waves exhibit most of the properties inherent to waves of other origins, including the excitation and propagation 21,22,23 , reflection and refraction 24,25,26,27,28,29 , interference and diffraction 30,31,32,33,34,35 , focusing and self-focusing 36,37,38,39,40,41 , tunnelling 42,43 , Doppler effect 44,45,46 , and formation of spin-wave envelope solitons 47,48,49,50 . Spin-wave quantization due to the finite size effect was discovered in thin films 51,52 and more recently in laterally confined magnetic structures 53,54,55,56,57,58 , with their effect upon the high frequency permeability and the observation of a negative permeability discussed in Refs.…”
Section: Spin Waves and Effectively Continuous Magnonic Metamaterialsmentioning
confidence: 99%
“…Spin waves exhibit most of the properties inherent to waves of other origins, including the excitation and propagation 21,22,23 , reflection and refraction 24,25,26,27,28,29 , interference and diffraction 30,31,32,33,34,35 , focusing and self-focusing 36,37,38,39,40,41 , tunnelling 42,43 , Doppler effect 44,45,46 , and formation of spin-wave envelope solitons 47,48,49,50 . Spin-wave quantization due to the finite size effect was discovered in thin films 51,52 and more recently in laterally confined magnetic structures 53,54,55,56,57,58 , with their effect upon the high frequency permeability and the observation of a negative permeability discussed in Refs.…”
Section: Spin Waves and Effectively Continuous Magnonic Metamaterialsmentioning
confidence: 99%
“…It has been shown that a moving wave packet can act as a flying qubit [23,24,25] like photon in a fiber. On the other hand, the analogues of optical device, beam splitter can be fabricated in quantum networks of bosonic [26], spin and ferimonic systems [27].…”
Section: Double-dot Qubitmentioning
confidence: 99%
“…We study the dynamics of various branched spin chain systems, showing how spatially separated entanglement can result from simple initial states. Branching has been considered for bosonic chains (coupled harmonic oscillators) [18,19] and for systems of propagating electrons [20,21]. Propagation of quantum states of Gaussian wave packet form was considered in these scenarios.…”
Section: Introductionmentioning
confidence: 99%